An estimation of the effective dose for the internal contamination of workers occupationally exposed to open sources of 131i in thyroid treatments - Lecuna, J.A.; Carrizales, L.I.; Dantas, B.M. (TECCIENCIA, 2014)
Handling a variety of unsealed sources in Nuclear Medicine has led to a significant risk of internal exposure for workers. 131I stands out among the radionuclides of frequent use due to its wide application in diagnosis and treatment of thyroid diseases. This study presents the development of in vivo bioassay techniques, in order to quantify the incorporation of 131I used in nuclear medicine. It also presents the results of research related to the internal exposure of a group of workers involved in handling therapeutic doses of 131I. The in vivo detection system was calibrated with a thyroid phantom developed at IRD (Brazil) which is also used at the UTN-IVIC (Venezuela). The workers monitored in this study presented measurable intake. Therefore, it is important to ensure future monitoring of such exposure. It also gives us the possibility of evaluating intake in cases of suspected accidents. The highest estimated effective dose was 1,28x10-5 Sv by inhalation and 1,27x10-5 Sv by ingestion. The proposed method showed enough sensitivity for its application in the assessment of the effective dose for 131I intake by workers. The minimum detectable effective dose associated with the MDA (244 to 287 Bq) is three orders of magnitude below the recording level of 1 mSv, considering a single intake by inhalation of a Type F compound of 131I in the form of vapor.